Evolutionary and genetic aspects of the plastome of oleaginous species - Lopes, Amanda de Santana (2018)
The plastid genome (plastome) is usually a circular molecule of about 150 kb and bears about 120 genes involved mainly in photosynthesis and gene expression. Its evolutionary trajectory includes structural rearrangements, gene degenerations, gene transfer to nucleus, positive selection, and events of gain and loss of RNA editing sites. These features are subject of interest in several areas of plant science such as phylogeny, evolution, basic research, and biotechnology. Additionally, plastomes bear a set of conserved genes useful for phylogenetic studies of deep relationships, so phylogenomic approaches based on whole plastomes have been also applied to resolve intrageneric relationships. Fast-evolving regions of plastid DNA such as intergenic spacers and introns, are source of molecular markers used routinely in phylogeographic and genetic studies. Finally, plastomes are a promising platform for biotechnological applications via plastid transformation. Over the last few years with the improvement of sequencing technology, many plastomes have been sequenced. Nevertheless, plastomes of several species belonging to different families remain unknown. Therefore, the purpose of this study was the sequencing of five plastomes of oleaginous species useful for different industry demands as follows: Linum ustitatissimum (Linaceae), Crambe abyssinica (Brassicaceae), Acrocomia aculeata, Astrocaryum murumuru, and A. aculeatum (Arecaceae). Here, it is presented a detailed characterization regarding molecular markers, phylogenetic inferences, and evolution. Molecular evolution analyses of protein- coding genes in Arecaceae show that highly divergent genes seem to evolve in a species- specific manner and more than half of the genes bear signatures of positive selection. Additionally, within Arecaceae and Linaceae were identified unique plastome rearrangements. It was also found events of gain and loss of RNA editing sites in all sequenced species, indicating a relatively high evolutionary rate of the RNA editing machinery. Hundreds molecular markers were identified in the plastomes sequenced here, providing information useful for several genetic studies aiming to stablish strategies for genetic breeding, domestication, and conservation of natural resources. Moreover, the phylogenies presented in this study, based on concatenated plastid genes or whole plastomes resulted in well-supported and well-resolved trees. Finally, this study sheds light on the evolutionary trajectory of plastomes, which give rise to questions about the relationships between environment adaptation and plastid gene expression.